3D Knee Trochlear Morphology Assessment by Magnetic Resonance Imaging in Patients With Normal and Dysplastic Trochleae. Issue 3 (March 2020) - Pennock, Andrew T.; Chang, Aileen; Doan, Joshua; Bomar, James D.; Edmonds, Eric W.
Abstract : Background: Trochlear dysplasia is recognized as a significant risk factor for patellar instability, but current imaging modalities fail to allow full visualization and classification of the complex 3-dimensional (3D) anatomy of the trochlea. The purpose of this study was to elucidate primary differences in trochlear morphology between patients with and without patellar instability by utilizing 3D magnetic resonance imaging (MRI) reconstructions of the trochlea. Methods: An institutional review board-approved retrospective review included 24 patients with a diagnosis of patellar instability and an age-matched and sex-matched control population of 12 patients. 3D models of the femoral trochlea were created from MRI images and measurements were performed. 3D measurements were trochlear groove volume and surface area that were normalized to the femoral width. 2D measurements were performed throughout the length of the trochlea including the bony and cartilaginous sulcus angles as well as the bony and cartilaginous trochlear depths. Differences were also assessed between sex, skeletal maturity, and trochlear dysplasia severity. Results: Surface topography of the trochlea varied significantly based on location with the trochlea becoming progressively more flat proximally away from the notch ( P <0.05). Patients with patella instability had reduced trochlear volumes and trochlear depths compared with control patients ( P <0.05). These differences were more pronounced with the cartilaginous measurements as well as more proximally within the trochlea. Patients with high-grade dysplasia had greater reductions in trochlear volumes and depth especially proximally in the trochlea ( P <0.05). Once femoral size was standardized, minimal differences were observed based on sex or skeletal maturity ( P >0.05). Conclusions: Novel 3D MRI reconstructions demonstrated that measurements of trochlear morphology varied significantly between patients with and without patellar instability. When trochlear dysplasia is present, it appears to affect the majority of the trochlear surface, but preferentially the proximal extent. Future trochlear dysplasia classification systems may benefit from assessment of articular cartilage surface measures rather than primarily osseous structure measurements. Level of Evidence: Level III—case-control prognostic study.